Development of Online Program Lesson on Designing Presentation and Picture Drafting by using the Iiiustrator Program for the Special Sportsman Students Program in mathayom ๕ - กันสุทธิ วันเพ็ญ; ละลอกน้ำ นคร; รักบำรุง ฐิติชัย (Journal of Educational Review Faculty of Education in MCU, 2019)
The objectives of this study aimed to develop online lessons using ILLUSTRATOR program to teach students about designing and presentation the stories, picture drafting especially for M.5 sportsman students program.1) To make the online lessons by using the illustrator program to improve the efficiency standard effect 90/902)To compare pre-test and post-test scores of the students who study the online program named MOODEL, the design and presentation of picture drafting by using illustrator program 3) To survey the learners’ satisfaction towards the online lesson named MOODEL, the design and presentation of picture drafting by using illustrator program. The population in this study was 30 students from 290 students who study in M.5 at Assumption College Sriracha . They were studying in the second semester of the academic year 2015, at Assumption College Sriracha , Chonburi province. It used the cluster sampling for choosing a classroom from 9 classrooms. The research instruments used in this study included with the online lesson, pre-test and post-test and the results from the learners’ satisfactions surveys. It was found that the development of the online program from the design and presentation of picture drafting by using illustrator program for M.5 sportsman students shows the efficiency by 99.17/93.33 then it follow with the setting criteria. The scores from post-test are higher than pre-test scores at the .05 level of significance and the students from the design and presentation of picture drafting by using illustrator program for M.5 sportsman students show the learners’ satisfactions at the highest level by the average rate is 4.52 and the SD rate is 0.57